Narration of Islamic Moderation: Counter over Negative Content on Social Media - S. Dinar Annisa Abdullah; Samudera Alfatra (Millati: Journal of Islamic Studies and Humanities, 2019)
This study tires to explore on how far the idea of Islamic moderation was adopted by Duta Damai of East Kalimantan in order to support a campaign of harmony in diversity. Using content analysis, this study tries to describe in depth the information content of Duta Damai community in East Kalimantan. The results of the study indicate that Duta Damai of East Kalimantan conducted counter-narratives of negative content on social media through opinions and statuses on social media, including: (1) alignment of Pancasila ideology with religious teachings, (2) revealing facts and education related to hoaxes ( 3) multicultural education campaigns and respect for differences, (4) actualization of the contemporary jihad. These four things are in line with the idea of Islamic, meaning that the community actualizes the idea of Islamic moderation in every campaign activity and movement. Through the tagline 'peace is Indonesia', Duta Damai of East Kalimantan want youth groups to actively campaign for the importance of positive speech and behavior and spread peaceful movement, both in the cyberspace and in the real world.